HUBUNGAN DURASI PENGGUNAAN GADGET TERHADAP TINGKAT KECEMASAN REMAJA SMK DI JAKARTA UTARA - Gracia Naftalie Ferdinand; Tri Setyaningsih; Dian Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gadget use among adolescents continues to increase alongside the development of digital technology, and excessive use is thought to affect psychological well-being, including increasing anxiety levels. This study aimed to determine the relationship between gadget usage duration and anxiety levels among vocational high school adolescents in North Jakarta. This study used a quantitative correlational design with a cross-sectional approach. The population consisted of 180 tenth- and eleventh-grade students at a vocational high school in North Jakarta, with a sample of 138 respondents selected using purposive sampling. Data were collected using a gadget usage duration questionnaire and the Zung Self-Rating Anxiety Scale (Z-SAS), then analyzed using univariate and bivariate analysis with the Spearman Rank correlation test at a significance level of α = 0.05. The results showed that the majority of respondents had a moderate duration of gadget use (50.7%), while the majority were in the non-anxious category (68.1%). The Spearman Rank test showed a correlation coefficient of r = -0.057 with a p-value of 0.503 (p > 0.05), indicating no significant relationship between gadget usage duration and anxiety levels among vocational high school adolescents in North Jakarta, with a negative direction and a very weak correlation strength. It is concluded that gadget usage duration is not the sole factor influencing adolescent anxiety, so other factors such as self-control, sleep quality, academic pressure, and social support should also be considered. Although not statistically significant, gadget use still needs to be monitored to prevent negative impacts on adolescents' physical and psychological health.